2016
DOI: 10.1038/cdd.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome dysfunction augments alternative polarization of alveolar macrophages

Abstract: The proteasome is a central regulatory hub for intracellular signaling by degrading numerous signaling mediators. Immunoproteasomes are specialized types of proteasomes involved in shaping adaptive immune responses, but their role in innate immune signaling is still elusive. Here, we analyzed immunoproteasome function for polarization of alveolar macrophages, highly specialized tissue macrophages of the alveolar lung surface. Classical activation (M1 polarization) of primary alveolar macrophages by LPS/IFNγ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 66 publications
(91 reference statements)
2
36
1
Order By: Relevance
“…They showed that inhibition of LMP7 increased M2 alternative activated macrophages by increasing their responsiveness to IL-4, while classical M1 macrophages were relatively unaltered. 49 These findings could open interesting perspectives in DMD while an important macrophagic component is always present within muscle fibers. Furthermore, a shift in macrophages polarization M1-M2 is observed from acute phase of 4-weeks to chronic stage, 12 weeks of age, where M2 macrophages are supposed to promote muscle repair by enhancing satellite cells proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…They showed that inhibition of LMP7 increased M2 alternative activated macrophages by increasing their responsiveness to IL-4, while classical M1 macrophages were relatively unaltered. 49 These findings could open interesting perspectives in DMD while an important macrophagic component is always present within muscle fibers. Furthermore, a shift in macrophages polarization M1-M2 is observed from acute phase of 4-weeks to chronic stage, 12 weeks of age, where M2 macrophages are supposed to promote muscle repair by enhancing satellite cells proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, M1phenotype prompts all the three subunits of immunoproteasome. On the other hand, alternatively activated M2 macrophages increases immunoproteasome activity by aggravating expression of LMP2 and LMP7 subunits only (Chen et al, 2016).…”
Section: Sepsismentioning
confidence: 98%
“…These cells express high levels of immunoproteasomes. While the proinflammatory IFN-␥/LPS-induced M1 phenotype was not changed in LMP7-deficient primary macrophages, IL-4 treatment of wild-type or LMP7-deficient cells resulted in augmented M2 polarization marker gene expression, increased M2 signaling (via STAT6 and AKT), and an increase in IL-4 receptor-␣ expression already at baseline (23). Catalytic inhibition of LMP7 with the immunoproteasome-specific inhibitor ONX-0914 led to similar results.…”
Section: Immunoproteasomes Shape Immune Cell Function and Innate Immumentioning
confidence: 71%
“…Special interest and conflicting data exist on the role of immunoproteasomes in NF-B signaling, which might reflect cell type-specific effects or the outcome of different experimental settings (44,49,72). Our own and partially unpublished data indicate that NF-B signaling is not affected by deletion of the immunoproteasome subunits LMP2 or LMP7: NF-B promotor-driven reporter gene as well as NF-B target gene expression were unchanged in alveolar macrophages of LMP2-deficient mice after LPS and IFN-␥induced macrophage polarization (23). Several mutations in the human PSMB8 and PSMB9 genes encoding the LMP7 and LMP2 immunoproteasome subunits, respectively, have been discovered in autoinflammatory disorders (1,4,17,62,70,74).…”
Section: Immunoproteasomes Shape Immune Cell Function and Innate Immumentioning
confidence: 74%